Internet Behavior and Safety Practices of Senior High School Students - Navarro, Lira (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the internet behavior of Senior High School (SHS) students and the internet safety practices implemented by SHS teachers in Mandaon District, Masbate. Anchored on Lev Vygotsky’s Sociocultural Theory, B.F. Skinner’s Behaviorism Learning Theory, and Jean Piaget’s Cognitive Development Theory, the study investigated the relationship between teachers’ internet safety practices and students’ internet behavior and served as the basis for developing an action plan to strengthen internet safety practices. A descriptive-correlational research design was employed using a researcher-made questionnaire validated for content and reliability. The respondents consisted of 69 Senior High School teachers selected through convenience sampling from eight public secondary schools in Mandaon District. Data were analyzed using the Weighted Mean and Spearman Rank Order Correlation Coefficient (ρ). The findings revealed that students generally demonstrated moderate internet competence, although responsible online behaviors such as media literacy, fact-checking, and protection of personal information were practiced only occasionally. Teachers consistently implemented internet safety practices in terms of online safety, digital literacy, resources and guidance, safe digital environments, and safe educational platforms. A weak but statistically significant positive relationship was found between teachers’ implementation of internet safety practices and students’ internet behaviors, indicating that increased teacher involvement is associated with more responsible online behavior. Based on the findings, an action plan was developed to strengthen digital citizenship, teacher capacity, parental involvement, and school-based internet safety initiatives. The study concludes that consistent teacher implementation of internet safety practices contributes to responsible internet behavior among students and recommends strengthening digital citizenship education, standardized teacher training, and collaborative stakeholder participation. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting digital literacy and safe learning environments, SDG 3: Good Health and Well-Being by encouraging responsible internet use that supports students’ well-being, and SDG 9: Industry, Innovation and Infrastructure through the effective integration of secure digital technologies in education. Its sustainability impact lies in strengthening educational, institutional, technological, and community efforts toward creating safe, inclusive, and sustainable digital learning environments.